Green synthesis and application of ZSM-5 zeolite - Chen, Ou (Array, 2021)
A ZSM-5 molecular sieve composite with a wide pore prepared by the solid phase in-situ synthesis method and fluid catalytic cracking, and an FCC catalyst additive prepared by the same ZSM-5 molecular sieve for increasing the amount of light olefin yield were investigated. The samples were characterized by XRD, N2 adsorption/desorption, SEM, and NH3-TPD, respectively. The results showed that the structure of the ZSM-5 molecular sieve composite prepared by solid phase in-situ synthesis method was pure MFI-type zeolite material. The crystallinity of ZSM-5 molecular sieve was 59.8 wt%. The synthesized ZSM-5 molecular sieve had more acid content and a wide-pore structure. The average pore size was 5.9 nm, and BET specific surface area and micropore specific surface area of sample were 213 m2 g–1 and 124 m2 g–1, respectively. The evaluated results indicated that the FCC catalyst additive had good selectivity for LPG, propylene, and butene, increasing propylene and butene yields by 2.28 wt% and 2.15 wt%, respectively, as well as had better heavy oil cracking capability and coke selectivity.